Living and learning: a sociocultural perspective and identity approach to foreign graduate students learning portuguese in Brazil - Oppelt, Camila Quevedo (2021)
Following the recent attention to less commonly taught languages, the interest in Portuguese as an additional language learning experienced an increase over the last decades (ABELEDO et al, 2014; AGUIAR, et al, 2013; BIZARRO, 2018; CARVALHO; SCHLATTER, 2011; FURTOSO; RIVERA, 2013; JÚDICE; ALMEIDA, 2013; OLIVEIRA, 2013; SHIBAYAMA, 2017; SILVA, 2010; SILVA; TOMÉ; TASSO, 2017). In recent years, the number of research studies greatly increased, particularly at academic level. However, there has been very limited reporting of research on the learning of Portuguese as additional language by foreign students attending graduate programs in Brazil. Since the increased interest in Portuguese language and in numbers of foreign students in Brazilian educational institutions, these two developments have not resulted in much attention. Constituting a gap, we believe the issue in question to be an appropriate subject to examine. Based on our main objective, to investigate the process of foreign students’ cultural and identity (re)constructions in learning Brazilian Portuguese as an additional language, we are specifically concerned with: (i) exploring to what degree participants’ language learning experiences change over time; (ii) exploring the expectations of foreign learners—including their imagined community(ies), imagined identity, historical memories, and cultural identity—and the extension of their influence on learner investment; and (iii) determining (power) relations established between foreign students and Brazilians in different interactions in Brazilian Portuguese (communications in a learning environment, exchanges in service encounters, etc.). as a theoretical reference, we assume Vygotsky’s (1978) perspective since it acknowledges the development of cognitive functions as directly related to social influence in the language learning/acquisition process. Relevant to this study, we highlight the studies of James Lantolf (2013) and Bonny Norton (1995, 1997, 2000, 2001, 2010, 2013a, 2013b, 2016) who formulated a Sociocultural Theory of Additional Language Development and contemplated the role of identity and of investment in the acquisition process, respectively. Participating in this study were four foreign graduate students at a public university in Southern Brazil. The four participants observed in this study were formally enrolled in the Agronomy Graduate Program at a Master’s or Doctoral level. Abdul, Jeremias, Pierre e Ramon were awarded a full scholarship which enabled them to live off-campus. The participants lived in shared houses; all but Jeremias and Pierre lived with other college students. Jeremias and Pierre lived in the same shared house, with another university student. Ultimately, we have sought to develop an enhanced understanding of the relationship between identity and language learning. Our analysis indicates a deeply intricate relationship amongst them, shedding light into the prominence of language development. Fortuitously, our participants seemed to have reached their ultimate purposes: they have all prospered in their academic and professional communities—may that by means of being awarded their sought degree (Pierre and Ramon), by concluding courses ministered in Portuguese (Abdul), by meeting the proficiency exam requirements, or even by being professionally promoted (Jeremias).